The evaluation of the effectivness of RESAN vaccine in the prophylaxis and the treatment of endometriosis – an experimental study with the animal model. Part II – prevention of the adhesions - Szymanowski, Krzysztof; Chmaj-Wierzchowska, Karolina; Niepsuj, Joanna; Yanchanka, Andrey; Florek, Ewa; Barlik, Magdalena; Opala, Tomasz (Menopause Review/Przegląd Menopauzalny, 2007)
Objective: The aim of our study was to evaluate the effectiveness of RESAN vaccine in prvention of adhesions formation in experimental animal study. Material and methods: The group of 58 sexually mature female rats was divided into three smaller groups. During the first step of experimet RESAN vaccine was injected among the group I of rats (n=24). Three months later during the 2-nd step of examination endometriosis was implanted in the groups I and II (n=24). Group III (n=10) was a control group where sham operations were performed. Three months after endometrial implants were removed and examined histologically. Meantime RESAN vaccine was injected as a treatment i the group II (step 3). Three months later an excision of the suspected foci was performed with histological examination of the tissue samples (step 4). Results: During the 3 rd step we found peritoneal adhesions in 14 of 23 rats. In nine animals no adhesions were found. During the 4 th step of examination no macroscopic changes were found in the group I. Among the group II there were adhesions near the ectopic endometrium in 11 rats. Near the cut line there were adhesions in 6 rats. Three of the animals had the adhesions of both types. During the 4 th step of experiment only 3 rats had adhesions. There were no adhesions in the control group. Conclusion: Pre- and postoperative RESAN vaccination reduces adhesion formation in the animal model of endometriosis.